Pengaruh Kompetensi, Integritas, dan Pengalaman Auditor Terhadap Kualitas Audit Pada Kantor Inspektorat Aceh Tenggara Kutacane - Yunita Althin Natanael (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study aims to determine and analyze the effect of competence on audit quality at the Southeast Aceh Inspectorate Office. to determine and analyze the influence of integrity on audit quality at the Southeast Aceh Inspectorate Office. To find out and analyze the influence of competence, integrity, and experience on audit quality at the Southeast Aceh Inspectorate Office. The research approach is quantitative associative research. In this study, the data analysis technique used was multiple linear regression analysis with the help of SPSS 15 software. Before analyzing the data, for the purposes of analyzing the data, the classical assumption test was first performed. Based on the results of the study, partially there is no effect of competence on audit quality at the Southeast Aceh Inspectorate Office, Partially there is the effect of integrity and experience on audit quality at the Southeast Aceh Inspectorate Office, then simultaneously there is the effect of competence, integrity, and experience on audit quality at the Office Southeast Aceh Inspectorate